APPLICATION OF PBL MODEL TO IMPROVE STUDENTS' LEARNING ACTIVITIES IN SCIENCE SUBJECT CLASS V SDI ENDE 9 - Nining Sariyyah; Agustina Sura Langkamau (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to improve the learning activities of grade V students of SDI Ende 9 through the application of the PBL learning model in science subjects. This type of research is classroom action research with stages of planning, action and observation. The subjects of the study were 11 students in class V. Data was taken by observation and documentation techniques. The data was analyzed to compare the percentage of learning activity results against performance indicators in this study. The results of the study show that after the implementation of the PBL learning model, the learning activities of students in science learning 43.75% in the first cycle became 100% in the second cycle. Science learning activities in the first cycle are in the less active category, and increased to the very active category in the second cycle. Thus, the application of the PBL learning model can increase student learning activities.